Distribution network hosting capacity assessment: Incorporating probabilistic harmonic distortion limits using chance constrained optimal power flow. Issue 2 (13th September 2021) - Sun, Wei; Harrison, Gareth P.
Abstract: The capacity of renewable distributed generation (DG) connected in distribution networks is increasing. Use of power electronic interfaces means DG can inject harmonic currents through the point of common coupling into upstream networks. The limits stipulated in harmonic emission standards may create challenges for accommodating DG. To explore the impact of harmonic regulations on the ability of distribution networks to host DG, this work incorporates harmonic voltage constraints into a network hosting capacity assessment. A novel hosting capacity assessment approach is presented, incorporating percentile‐based harmonic compliance levels as chance constraints over multiple periods into AC optimal power flow. The case study shows that network hosting capacity for DG could be evidently lower under rigorous compliance with harmonic distortion limits, but that relaxation of the risk constraints has significant value. Furthermore, the complex inter‐connectivity between DG sites means that voltage, thermal and harmonic constraints all influence the locational feasibility for DG capacity.